Enhancing Reading Literacy through Augmented Reality among Indonesian Migrant Children in Malaysia - Laksana, Sigit Dwi; Setyosari, Punaji; Praherdhiono, Henry; Kuswandi, Dedi; Priatna, Yolan; Abidin, Nurul; Kholis, Kholis; Hile, Abdulhafiz (Journal of Integrated Elementary Education, 2025)
Indonesia continues to face persistent challenges in reading literacy, particularly among children of migrant workers who lack access to quality formal education. This study explores the effectiveness of Augmented Reality (AR)-based learning media in enhancing the reading skills of Indonesian migrant children in Malaysia. Utilizing a quantitative pretest-posttest design, this study involved 34 elementary school students enrolled at At-Tanzil Learning Center in Selangor. The intervention consisted of interactive AR-enhanced picture storybooks, designed to improve reading motivation, letter and word recognition, and reading comprehension. Data were analyzed through simple linear regression analysis using SPSS. The findings revealed a statistically significant improvement in students' reading abilities after the use of AR media (t = 2.629, p = .012), with an R² value of 0.136, indicating a 13.6% effect size. The results suggest that AR integration into literacy instruction can meaningfully support early reading development, particularly in the reading skill aspect. Furthermore, the use of immersive and interactive technologies has been shown to increase student engagement, comprehension, and motivation to read. These outcomes underline the potential of AR as a pedagogical tool for marginalized populations and offer practical implications for educators, policymakers, and instructional designers aiming to bridge literacy gaps through accessible and technology-supported interventions. This study contributes to the growing body of research on digital learning innovations and highlights the role of AR in promoting inclusive literacy education across transnational and underserved contexts.